Revival: a history of the art of War in the sixteenth century (1937) - Charles, Oman., author.
1 online resource (824 pages).
Keywords: In the beginning of the time period concerned, we are still in the Middle Ages – Flodden Field or Novara might almost have been fought in the fifteenth century. At the end a formal battle like Nieuport might almost have been fought in the Thirty Years War. This volume is the result of an attempt to sum up the fundamental alterations in the Art of War between 1494 and 1600, and is intended to serve as an outline of military theory and practice between those dates.